Enraizamiento de varetas de pitahaya amarilla (Selenicereus megalanthus) en función del tamaño y uso de fitorreguladores - Zambrano Salas, Jorge Patricio (2024)
The present study was carried out on the ESPAM MFL campus, located in Cantón Bolívar, Manabí, Ecuador. The objective was to evaluate the rooting of yellow pitahaya (Selenicereus megalanthus) based on the two sizes of rods and the use of three rooters. A DBCA design with AxB+2 factorial arrangement was used. The treatments were made up of the following: T1 (ÁIB + 30 cm dowels), T2 (ÁIB + 15 cm dowels), T3 (ÁIB + 30 cm dowels), T4 (ÁIB + 15 cm dowels), T5 (Cytokinins + 30 cm rods), T6 (Cytokinins + 15 cm rods), T7 (Without rooting agent + 30 cm rods) and T8 (Without rooting agent + 15 cm rods). Statistical analysis was performed using Infostat software, using the Tukey test at 0.05% significance level. The results showed significant differences (p<0.05) in the variables days of shoot emission and root length, and highly significant differences (p<0.01) in the variables shoot weight, shoot volume, shoot length, shoot diameter. and root weight. And no statistical differences were found in the variables number of sprouts and percentage of twigs lit. T1 turned out to be the best treatment, achieving the best results in percentage of shoots attached, shoot length, shoot diameter, shoot weight, shoot volume and root weight. Based on this research, the application of ANA and the use of 30 cm rods is recommended.